Contemporary practice and outcomes of an elderly cohort of Japanese patients with non-ST-elevation acute coronary syndrome in the era of routine early invasive strategy. (1st August 2017) - Nagata, Takuya; Hyakuna, Yohei; Miyata, Kenji; Mohri, Masahiro
Abstract: Background: An early invasive strategy for patients with non-ST-segment elevation acute coronary syndrome (NSTE-ACS) has been recommended. However, patients at greater risk including the elderly are more often managed conservatively. We aimed to elucidate contemporary practice and outcomes of patients with NSTE-ACS who were referred to our hospital located in Kitakyushu City, one of the most aging metropolises in Japan. Methods: A total of 270 consecutive NSTE-ACS patients hospitalized between January 2012 and December 2014 were retrospectively studied. Results: Median [interquartile range] age was 73 [64, 80] years. Coronary angiography was performed in 264 (98%) patients. Importantly, 75% and 89% underwent angiography within 24 h and 72 h after admission, respectively. Revascularization was done in 124 (79%). The all-cause, in-hospital mortality was 3.7% and was higher in patients aged ≥ 80 years (8.5% vs. 2.0% in those aged < 80 years, p  < 0.0001). No patient developed major bleeding or stroke during hospitalization. Killip class IV at presentation (odds ratio [OR] 8.77, 95% confidence intervals [CI] 1.64–47.6) and left main trunk disease (OR 7.58, 95% CI 1.28–45.5) were independently associated with in-hospital death. These two variables and a high (≥ 140) GRACE score were associated with a higher 1-year mortality by Kaplan-Meier survival analysis ( p  < 0.0001). Conclusions: An early invasive strategy was safely done in an elderly cohort of Japanese patients with NSTE-ACS. In addition to early invasive approach, a further therapeutic strategy, most probably targeting a shock status, is needed to improve both short- and long-term survival.